Solidification/Stabilization of Textile Sludge as Subgrade: Usage of Binders and Skeleton Material - Xiao Cheng; Bingyi Li; Geng Chen; Shihu Gao (Advances in Civil Engineering)
This study investigates the disposal of textile sludge via laboratory and field tests while protecting the eco-environment. Solidification/stabilization (S/S) technology and skeleton construction method are introduced to investigate the application of S/S sludge for subgrade material. S/S is to enhance the sludge strength and stabilize the metal(loid)s and hazardous organics in the textile sludge. Skeleton construction method aims to decrease the liquid-solid ratio in mixture to reduce the binder dosage and save binder cost. In the laboratory, binders and skeleton material are implemented to investigate the differences in unconfined compressive strength (UCS) to explore the optimal mixture. Results illustrate that UCS of binder-sludge is below 100 kPa and enhanced more than 400 kPa after adding gypsum and skeleton material. Skeleton soil material with high plasticity index and low moisture content improves UCS significantly. Scanning electron microscopy test shows the physical microstructure of sludge is greatly improved for the particular space grid structure formed by the particles and cementitious products. The leaching test shows the metal(loid)s and organics in leachate are decreased after S/S treatment and below the standard value. Finally, the textile sludge was disposed for subgrade via the technology. The strength and leaching results of field tests are in good agreement with the laboratory results. The bearing capacity of the practical subgrade meets the design requirements.